Spontaneous Mirror‐Symmetry Breaking in Isotropic Liquid Phases of Photoisomerizable Achiral Molecules. Issue 1 (22nd October 2015) - Alaasar, Mohamed; Prehm, Marko; Cao, Yu; Liu, Feng; Tschierske, Carsten
Abstract: Spontaneous mirror‐symmetry breaking is of fundamental importance in science as it contributes to the development of chiral superstructures and new materials and has a major impact on the discussion around the emergence of uniform chirality in biological systems. Herein we report chirality synchronization, leading to spontaneous chiral conglomerate formation in isotropic liquids of achiral and photoisomerizable azobenzene‐based rod‐like molecules. The position of fluorine substituents at the aromatic core is found to have a significant effect on the stability and the temperature range of these chiral liquids. Moreover, these liquid conglomerates occur in a new phase sequence adjacent to a 3D tetragonal mesophase. Abstract : Let's twist again : Chirality synchronization leads to spontaneous conglomerate formation of domains with opposite chirality in isotropic liquids of specifically designed achiral azobenzene‐based molecules. Fluorination of the aromatic core was a powerful tool to tailor the temperature range of these spontaneously chiral liquids. The liquid conglomerates occur in a new phase sequence adjacent to 3D tetragonal mesophases.